Peran Guru Pendidikan Agama Islam Dalam Membentuk Karakter Dan Disiplin Ibadah Peserta Didik Pada Masa Pasca Pandemi Covid-19 - Salsabila Mukhtar; Andrianto Andrianto; Sumiarti Sumiarti; Nora Afnita; Syamsurizal Syamsurizal (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
This research aims to : This research method uses qualitative with a descriptive approach, with data collection through observation, in-depth interviews as the main data collection tool and documentation as supporting data. Data analysis techniques used by collecting data, summarising data, presenting the data and drawing conclusions from the data that has been processed. The results of this study show that Islamic Religious Education teachers at SMAN 5 Pariaman play an important role in shaping students' character through an inclusive and interactive approach. They provide real examples of Islamic values to be applied in daily life and provide strong moral support and motivation to students. In addition, Islamic Education teachers also play a role in helping learners understand and practice worship consistently, even in distance learning situations. The role of Islamic Education teachers at SMAN 5 Pariaman is very important in shaping students' character and their worship discipline, especially in the post-COVID-19 pandemic period. The results of this study provide valuable insights into how Islamic religious education can continue to adapt to changing times and have a positive impact on student development. The implication of this research is the need to continue to support and develop the role of Islamic Religious Education teachers in Islamic religious education in the future.